EVALUATION OF ORAL HEALTH EDUCATION INTERVENTION ON ORAL HYGIENE STATUS AMONG HIGH SCHOOL STUDENTS - SHAHAPUR R P; SHAHAPUR P R (International Journal of Pharma and Bio Sciences, 2013)
Health education aims to improve knowledge regarding oral health which helps in developing posititve attitude and favourable oral health behavior.Aim: The present study was aimed to assess the effectiveness of oral health education on oral hygiene status of students.Methodology: An interventional trial was conducted. Base line data on oral hygiene status was recorded using Silness and Loe plaque index. Health education was given to them with the help of audiovisual aids. Plaque values were again recorded after 4 weeks of the interventional health education session.Results: A total of 109(41-F and 68-M) students aged13, 14and 15 years participated in the study. Mean scores of plaque at base line and after 4 weeks were 1.7697± 0.7904 and 1.3779±0.6537 respectively. Conclusion: Statistically significant reduction was observed in plaque scores after the short session of health education. Females had lower plaque scores than males both at baseline and after 4 week observations.